102 THE REPRODUCIBILITY AND ANALYSIS TIME OF CARDIAC MAGNETIC RESONANCE FEATURE TRACKING: POTENTIAL FOR CLINICAL APPLICATION. (24th May 2013) - Taylor, R J; Umar, F; Moody, W E; Townend, J; Steeds, R P; Leyva, F
Abstract : Background: Myocardial strain imaging has the potential for clinical application in the detection of pre-clinical disease, stress induced myocardial dysfunction and dyssynchrony. Feature-tracking cardiovascular magnetic resonance (FT-CMR) uses routine CMR imaging (steady-state free-precession imaging) to calculate myocardial strain. Methods: Healthy volunteers (n=20, age: 42±13 years, 11 (55%) male) underwent a standard protocol CMR. Endocardial and epicardial borders were manually drawn and automatically tracked through the cardiac cycle.Figure 1 Results: As shown in the Table, circumferential strain (Ecc ) was the most reproducible, followed by longitudinal strain (ELL ) and radial strain (Err ). FT-CMR analysis time was 3±1 mins. Conclusions: FT-CMR is highly reproducible within operators, particularly with respect to Ecc . This, together with a short time required for analysis, enhances the potential of this imaging modality in clinical practice.